Influence of heating temperature, pressure and pH on recrystallization inhibition activity of antifreeze protein type III. (October 2016) - Leiter, Andreas; Rau, Stefanie; Winger, Sebastian; Muhle-Goll, Claudia; Luy, Burkhard; Gaukel, Volker
Abstract: The objective of this work was to investigate the influence of heating temperature, pressure and pH on ice recrystallization inhibition (IRI) activity and on the structure of fish antifreeze protein type III (AFP III). Results showed that temperature treatment up to 80 °C for one minute had no influence on IRI activity. 1 H NMR spectroscopy demonstrated a fully reversible denaturation after temperature treatment at 80 °C up to 1 h. Adjusting pH with hydrochloric acid or sodium hydroxide increased the IRI activity independent of the pH value, whereas NMR experiments showed no significant structural change. Experiments with sodium chloride showed that the addition of ions is responsible for increased IRI activity and increasing ion concentration led to increased IRI activity up to a limiting value between 0.02 and 0.03 M. Pressure treatment up to 400 MPa for one minute had no influence on IRI activity. Highlights: Short heating time up to 80 °C has no significant influence on IRI activity of AFP III. Thermal denaturation of AFP III is fully reversible after heat treatment at 80 °C. Increased IRI activity with increasing ion concentration up to a limiting value. Short pressure treatment up to 400 MPa has no significant influence on IRI activity.